(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-98-106 In this article, the author applies the theory of primary speech genres by M. M. Bakhtin, developed by A. D. Stepanov, exploring the work of A. N. Ostrovsky. The focus is on Ostrovsky’s use of the compliment genre. The comedies of different periods of the playwright’s work are studied (“Let’s count our own people!”, “An unexpected case”, “Simplicity is enough for any wise man”, “Talents and fans”). Referring to the works of linguists, the author notes that the use of a compliment may indicate the insincerity of the interlocutor. Ostrovsky’s plays, according to the author, also reflect a negative attitude towards a compliment. It is expressed in the fact that the use of Ostrovsky’s characters of this genre is inextricably linked either with their selfish motives and, indeed, insincerity (Podkhalyuzin, Glumov, Berkutov), or with others, also bad intentions (Dulebov and Velikatov), or with frivolity (Rozoviy) and helplessness (Narokov). Ostrovsky’s serious and honest characters do not resort to compliments (Meluzov). Thus, the use or nonuse of a compliment by a character can serve as a marker of his moral qualities. Having studied the use of the compliment speech genre in Ostrovsky’s work, the author suggests that the application of the theory of speech genres in the study of the playwright’s work in the future may bring a new look at the characters he created. Key words: speech genre, Ostrovsky, compliment, comedy, insincerity